Advertising Special Project in Online Media: Characteristics of Phenomenon in Russian Research - K. A. Boldina (Научный диалог, 2022)
A review of Russian studies, which are devoted to the study of the content and structural features of advertising special projects, is made. This phenomenon is at the intersection of multimedia journalism, digital marketing and Public Relations. It has not yet received a clear definition and does not have a strict classification due to the dynamic development within the last decade (since the first examples of special projects appeared in 2012). At the same time, special projects can be called one of the permanent areas of the editorial offices work of modern Russian online media. Creating special projects for brands allows the media to maintain self-sufficiency by providing a creative and most effective advertising service. An overview of the Russian scientists’ opinion on the distinctive characteristics of the special project from other journalistic materials is included in the article. It contains options for interpreting the definition of “advertising special project” and options for the kinds and types of the phenomenon. It is concluded that researchers attribute special projects to non-standard media materials, note their integrative nature, attraction to multimedia and the mandatory presence of marketing goals.